The effect of epigenetic factors on differentiation of pancreatic progenitor cells into insulin-producing cells - Leontovyč, I; Koblas, T; Pektorova, L; Zacharovova, K; Berkova, Z; Saudek, F (Transplantation proceedings, 2011)
Differentiation of pancreatic progenitors into insulin-producing β cells is regulated by various transcription factors. To be expressed the genes coding these transcription factors need to be in accessible DNA. Whether a particular gene is present in a form of active euchromatin structure with accessible DNA or in an inactive heterochromatin structure with inaccessible DNA is determined by various epigenetic modifications. We studied the effect of epigenetic modifiers on differentiation of human nonendocrine cells into insulin-producing cells with the aim to evaluate the effect of epigenetic modifications in that process. Within 3 days of cultivation nonendocrine cells form isletlike cell clusters (ILCCs) containing mainly cytokeratin-19-positive cells. After cultivation with epigenetic modifiers and further differentiation, the highest number of C-peptide-positive cells (10.3% ± 2.9%) as well as glucagon-positive cells (7.2% ± 2.8%) was observed in a sample supplemented with a combination of 5-Aza-2'-deoxycytidine modifiers, BIX01294 and MC1568. In response to glucose stimulation (5 vs 20 mmol/L) these ILCCs secreted increased amounts of C-peptide (0.45 vs 1.05 pmol C-peptide/μg DNA). Control samples treated without any epigenetic modifiers showed significantly lower numbers of C-peptide-positive cells (3.5% ± 1.6%). These results showed that a combination of epigenetic modifiers 5-Aza-2'-deoxycytidine (BIX01294 and MC1568) significantly improved reproducible differentiation of nonendocrine pancreatic cells into insulin-producing cells.
Keywords: beta-buňky; Models, Genetic; Pancreas; C-Peptide; modely genetické; Keratin-19; Quinazolines; Cell Differentiation; epigeneze genetická; Azepines; Cell Culture Techniques; lidé; Epigenesis, Genetic; imunohistochemie; Islets of Langerhans; Transcription Factors; azacytidin; Langerhansovy ostrůvky; Pyrroles; chinazoliny; Models, Biological; transkripční faktory; Immunohistochemistry; keratin-19; Humans; azepiny; kyseliny hydroxamové; Insulin-Secreting Cells; biologické modely; buněčné kultury; Stem Cells; Decitabine; C-peptid; buněčná diferenciace; kmenové buňky; Azacitidine; pankreas; pyrroly; decitabin; Hydroxamic Acids